AKTIVITAS SITOTOKSIK FRAKSI n-HEKSANA : KLOROFORM DARI EKSTRAK METANOL KULIT BATANG MANGROVE (Rhizopora mucronata) PADA SEL KANKER MYELOMA - Harwoko Harwoko; Esti Dyah Utami (Majalah Obat Tradisional, 2010)
The Mangrove plants have been long used for traditional medicine to cure gastroenteritis and cancer theraphy. Rhizopora mucronata, one species of Mangrove, is still rare studied that have potention as anti cancer. This research goals was to fractination bioactive compound of R. mucronata with various organic solvent and cytotoxicity test of those fraction n-heksana : chloroform to cancer cell myeloma. The extract from R. mucronata stem barks was made by maseration with methanol. The extracts was partitioned with chloroform, etil acetate, and methanol. The fraction of chloroform was fractination with n-heksana : chloroform (3 : 2). The fraction respectively was examined their cytotoxicity on Myeloma cell-line by MTT methods.  Result showed that fraction n-heksana : chloroform from methanolic extract of R. mucronata stem barks was toxic on Myeloma cell, with the IC50 value was 15 µg/mLand phytochemical study showed that the active fractions contained flavonoid and terpenoid.